The Criminal Trial of Melchior Wańkowicz - Łuczak, Maciej (Porównania, 2025)
The criminal trial of Melchior Wańkowicz was a show trial. It was a form of repression for the writer’s signing of the Letter of 34 and for his publicly expressed criticism of the cultural policy of the Polish People’s Republic’s authorities. The Security Service took over Wańkowicz’s study on limiting freedom of speech and censorship. On November 9, 1964, the writer was sentenced to 18 months of rigorous imprisonment for disseminating false information that harmed the interests of the state. Wańkowicz renounced his American citizenship and instead of appealing the sentence, he wrote a letter to the First Secretary of the Central Committee of the Polish United Workers’ Party, Władysław Gomułka. As a result, they met and by Gomułka’s personal decision, the sentence of absolute imprisonment was never carried out, allowing Wańkowicz to continue publishing his books and participate in cultural life again.